Intravenous Laser Therapy in Young Children with Thermal Injuries - R. V. Bocharov (Общая реаниматология)
Objective: to evaluate the laboratory and clinical effects of combined intravenous laser therapy in young children with thermalinjuries in the acute period of burn disease.Subjects and methods. Forty children whose mean age was 2.67±0.35 years were examined; thermal injuries accounted for 25.05±1.01% of the total body surface area; of them degrees IIIaIIIb was 19.04±0.85%. A comparison group (n=15) received conventional therapy without taking into account and correcting baseline and current hemostasiological disorders. On day 1, a study group (n=25) had programmed anticoagulant therapy and intravenous laser therapy at different radiation frequencies with a Mustang 20002+ laser therapy apparatus (patent for invention No. 2482894) in addition to the conventional therapy. The laser therapy cycle was 6 to 16 sessions. The investigators estimated and compared the following examined parameters: white blood cell count; leukocytic index of intoxication; plasma average mass molecules at a wavelength of 254 nm; toxogenic granularity of neutrophils; wound exudate discharge time; surgical plasty area; and hospitalization time.Results. The positive laboratory and clinical effects of the performed combined intravenous laser therapy in the combined therapy of burn disease in young children were comparatively shown in the study group patients. The significant decrease in the level of an inflammatory response and endogenous intoxication led to a rapider burn wound cleansing, active epithelization, and reduced surgical plasty volumes.Conclusion. Combined intravenous laser therapy signif icantly exerts antiinflammatory and detoxifying effects in young children with 40% thermal injuries in the acute period of burn disease. Abolishing a systemic inflammatory response by combined intravenous laser therapy initiated early regenerative processes in the burn wound and caused reductions in surgical plasty volumes and hospitalization time, which optimizes ther apy for burn disease.